2018
DOI: 10.2147/cia.s176899
|View full text |Cite
|
Sign up to set email alerts
|

American Geriatrics Society-Beers Criteria and adverse drug reactions: a comparative cross-sectional study of Nigerian and South African older inpatients

Abstract: BackgroundThe Beers Criteria were developed with the aim of improving the safety of medicines among older persons. While the association between the Beers’ list of potentially inappropriate medicines (PIMs) and adverse drug reactions (ADRs) among older Caucasians is contentious, the ability of the Criteria to predict ADRs among older persons in Africa remains unexplored.ObjectivesThis study aimed to compare the prevalence of PIMs and ADRs among hospitalized older persons in Nigeria and South Africa, and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The body of research in the area of prescription of potentially inappropriate medications and its consequences in elderly patients continues to grow in developing countries, like Nigeria and South Africa (Fadare et al, 2013; Fadare et al, 2015; Van Heerden et al, 2016; Akande-Sholabi et al, 2018; Saka et al, 2018). With improvement in the management of communicable diseases, such as HIV/AIDS, malaria, and tuberculosis, people are living longer in many developing countries and as such the proportion of elderly patients is expected to rise significantly in the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…The body of research in the area of prescription of potentially inappropriate medications and its consequences in elderly patients continues to grow in developing countries, like Nigeria and South Africa (Fadare et al, 2013; Fadare et al, 2015; Van Heerden et al, 2016; Akande-Sholabi et al, 2018; Saka et al, 2018). With improvement in the management of communicable diseases, such as HIV/AIDS, malaria, and tuberculosis, people are living longer in many developing countries and as such the proportion of elderly patients is expected to rise significantly in the next decade.…”
Section: Introductionmentioning
confidence: 99%
“…First, the 2015 AGS‐Beers Criteria original recommendations with the caveats were included in the survey, with special consideration for the medicines reported to be commonly inappropriately prescribed among Africans . Secondly, some of the parent recommendations were modified based on the observation of a previous study by the research team that showed associations between certain AGS‐Beers potential inappropriate medications (PIMs) and adverse drug reactions (ADRs) among older inpatients in Nigeria and South Africa . For instance, the 2015 AGS‐Beers Criteria recommend spironolactone to be avoided in renal impairment (Crcl < 30 mL/min), but based on the finding of the above study, the threshold for renal impairment was increased to <60 mL/min in this present study.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the 2015 AGS‐Beers Criteria recommend spironolactone to be avoided in renal impairment (Crcl < 30 mL/min), but based on the finding of the above study, the threshold for renal impairment was increased to <60 mL/min in this present study. Tramadol was also recommended to be “avoided” against cautious use stipulated in the 2015 AGS‐Beers Criteria based on the finding of the above‐cited study …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations